Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/s00425-003-0992-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of sulfoquinovosyl diacylglycerol in the structural integrity and heat-tolerance of photosystem II

Abstract: To examine the role of sulfoquinovosyl diacylglycerol (SQDG) in thylakoid membranes, we compared the structural and functional properties of photosystem II (PSII) between a mutant of Chlamydomonas reinhardtii defective in SQDG (hf-2) and the wild type. The PSII core complex of hf-2, as compared with that of the wild type, showed structural fragility when solubilized with a detergent, dodecyl b-Dmaltoside, suggesting that the physical properties of the PSII complex were altered by the loss of SQDG. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…Similar observations, i.e. the lowered specific activity of PSII and the enhanced sensitivity to DCMU, were made for SQDG-deficient mutants of C. reinhardtii [9,10,31]. Yu et al [32] also indicated that the effective quantum yield of PSII was slightly but significantly reduced in SQDG-deficient mutants of Arabidopsis thaliana.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar observations, i.e. the lowered specific activity of PSII and the enhanced sensitivity to DCMU, were made for SQDG-deficient mutants of C. reinhardtii [9,10,31]. Yu et al [32] also indicated that the effective quantum yield of PSII was slightly but significantly reduced in SQDG-deficient mutants of Arabidopsis thaliana.…”
Section: Discussionsupporting
confidence: 63%
“…However, the conclusion drawn from in vitro experiments is not necessarily valid in vivo.The mutants of some lipid metabolism pathways have proved to be useful tools for investigating in vivo the specific roles of lipids in photosynthesis. A mutant of Chlamydomonas reinhardtii, defective in SQDG (hf-2), showed PSII activity that was 40% lower than that of the wild-type, an increase in sensitivity of the PSII activity to 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), and a lower growth rate [9][10][11][12]. In accordance with these observations, the incubation of isolated thylakoid membranes of hf-2 with SQDG in vitro reversed the lowered PSII activity.…”
mentioning
confidence: 99%
“…This observation may be interpreted as a response to adjust the membrane fluidity of photosynthetic membranes. PUFAs in membranes are also important for adjusting membrane fluidity during shifts in salinity and light intensity [75]. It has been shown that a temperature-shift from 25 to 10 °C will enhance the proportion of PUFAs, especially EPA, by 120% in P. tricornutum [76].…”
Section: Chromista and Their Lc-pufa Content And Functionmentioning
confidence: 99%
“…Because LC-PUFAs are enriched in galactosylglycerides such as SQDG and M/DGDG in the thylakoid membranes, it is assumed that they contribute to the photosynthetic function of algae. For instance, studies of the green algae Chlamydomondas reinhardtii showed the importance of the glycosylglyceride SQDG for maintaining photosystem II functionality during environmental changes (e.g., temperature), and thus indicates, as well, a role of PUFAs in maintaining the photosynthetic machinery [75]. …”
Section: Chromista and Their Lc-pufa Content And Functionmentioning
confidence: 99%
“…Sulfoquinovosyl diacylglycerol (SQDG) is one of the membrane lipids specific to chloroplasts, and is responsible for the structural and functional integrity of the photosystem II complex in C. reinhardtii (Sato et al, 1995, 2003a; Minoda et al, 2003; Sato, 2004). Intriguingly, we recently reported that cells of C. reinhardtii degrade SQDG for utilization of it as a major intracellular sulfur (S)-source for the synthesis of protein, especially at an early phase of S-starvation (Sugimoto et al, 2007, 2008, 2010).…”
Section: Introductionmentioning
confidence: 99%